Visualizing the Real Time Reduction of Pulled Elbow Using Point of Care Ultrasound (POCUS) - David McCreary (CINQUILL Medical Publishers Inc., 2024)
POCUS is a useful tool for correctly identifying pulled elbow. We believe that clinicians working in Pediatric Emergency Departments should be encouraged to embrace using it in cases which are less straightforward - either due to an atypical history or based on examination findings. This will serve to not only increase safety and improve the patient journey, but also to improve the clinician's confidence in their practice. This is the first ever documented instance where the reduction of pulled elbow has been demonstrated in real time using POCUS.